Conoce la evolución (2020)
Internships are a tool used by Universities for their senior students to experiment and have an approach to them facing off in the world of work, and in this work, we will see how my experience was in LA MUESTRA team and how was the change and progress that was made through it throughout the semester as they were practices as I had not imagined them and that posed several challenges that were overcame